Meningkatkan Kesadaran Masyarakat Terhadap Kesehatan Dan Mengedukasi Dalam Ilmu Pengetahuan Umum Dan Pengelolaan Umkm Menuju Kawasan Sehat, Mandiri Dan Religius - Pagala, Ashar (TAFANI: Jurnal Pengabdian Masyarakat, 2022)
Sultan Aji Muhammad Idris State Islamic University (UINSI) Samarinda as one of the State Universities in Indonesia is expected to be able to play a role in implementing the values ​​of the Tri Dharma of Higher Education, namely the dharma of education and teaching, the dharma of research and the dharma of community service. LP2M as a research and community service center is responsible for organizing the Field Work Lecture program. On this occasion, we raised the theme "Efforts to Increase Public Awareness of Health and Educate in General Science and Management of MSMEs in the Framework of Towards a Healthy, Independent and Religious Area in Sungai Dama Village". Community service activities with this theme are community empowerment activities through the active role of students as a real movement in the community that is used as a partner to carry out activities that lead to community empowerment to realize independence, prosperity, and give birth to a generation with good character. Morals occupy a very important position in Islam so that every aspect is taught to be oriented towards the formation and development of noble character. One of the implementations of these values ​​is through education. Not only has a lot of knowledge but also has manners, manners and respect for fellow human beings. 1. Conducting field surveys and seeking information about the local area to the lurah. 2. Compile a work program according to the Real Work Lecture Technical Guidebook (KKN-B). 3. Conduct consultations and ask for direction from LP2M regarding the work program to be implemented. 4. Confirming the work program to be carried out to the Lurah Sungai Dama. 5. Implement the work program that has been planned. 1. Implementation of Semi-Regular KKN Semi-Regular KKN is a KKN that is carried out directly in the community as well as Regular KKN, only KKN participants are not allowed to establish KKN POSKO. Semi Regular KKN participants are students who live in the local KKN area. The program we carry out consists of 6 aspects, including: a. Religious aspects, b. Educational aspects c. Economic empowerment aspects, d. Health aspects, e. Social participation aspects, f. Community needs. Community participation and support is quite high, where the community is actively involved in implementing the program so that the community can take maximum advantage of it. We hope that the various work programs in KKN can provide many benefits for KKN students and the residents of Sungai Dama Village, especially in the religious field. Keywords: Health, Educate, Healthy, Independent, Religious